Identification of Sludge Production In Water Treatment Installations of Urban Drinking Water Companies - Rifka Noor Azizah; Trian Saputri; Wisnu Prayogo (Journal of Community Based Environmental Engineering and Management, 2022)
The by-product of sludge generated at the Water Treatment Plant can affect water quality degradation if disposed of directly without any prior treatment. As a company engaged in water management, the urban drinking water companies produce sludge in every production activity. This study aimed to identify the flow of sludge generation at the Water Treatment Plant, the quantity of sludge generated at the sedimentation unit, and the quality of the wastewater generated at the Sludge Treatment Plant. The identification results show that the flocculation, sedimentation, and filtration units produce sludge transported to the sludge treatment unit (SCP and SDB). The quantity of sludge generated in the sedimentation unit in March and April are 1,887m3/day and 1,474m3/day, respectively. The physical and chemical quality (pH, temperature, TDS) of wastewater produced by the sludge treatment unit are still below the quality standard based on PERMENLHK No. 5 of 2014, concerning Wastewater Quality Standards for Businesses or Activities That Do Not Have Wastewater Quality Standards.